Modeling economic growth in contemporary Indonesia - Sergi, Bruno S.; Sulistiawan, Dedhy (Entrepreneurship and global economic growth., 2022)
This new volume of the Entrepreneurship and Global Economic Growth series explores Indonesia's most recent business and economic developments. Modeling Economic Growth in Contemporary Indonesia has chapters covering topics such as SMEs, public companies, stock markets, government, or non-profit organizations to explain economic growth and factors. Modeling Economic Growth in Contemporary Indonesia chapters carefully addresses economic growth in contemporary Indonesia. Since the Asian monetary crisis in Indonesia has initiated reforms and its progress is substantial, becoming the largest economy in Southeast Asia and the world's 16th largest. Featuring empirical studies in management and organization along with market-based studies discussing the economic growth of contemporary Indonesia, chapters cover a broad range disciplines, including entrepreneurship, government support, family business, marketing strategy, stock market, poverty, and microfinance. Modeling Economic Growth in Contemporary Indonesia's analysis touches on timely, interdisciplinary subjects effecting both big and small cities in Indonesia while also highlighting the role of education in improving entrepreneurship.